Rapid and Ultrasensitive Detection of Mutations and Genes Relevant to Antimicrobial Resistance in Bacteria. Issue 2 (30th November 2020) - Huber, François; Lang, Hans Peter; Lang, Daniela; Wüthrich, Daniel; Hinić, Vladimira; Gerber, Christoph; Egli, Adrian; Meyer, Ernst
Abstract: The worldwide emergence of multidrug‐resistant (MDR) bacteria is associated with significant morbidity, mortality, and healthcare costs. Rapid and accurate diagnostic methods to detect antibiotic resistance are critical for antibiotic stewardship and infection control measurements. Here a cantilever nanosensor‐based diagnostic assay is shown to detect single nucleotide polymorphisms (SNPs) and genes associated with antibiotic resistance in Gram negative ( Pseudomonas aeruginosa ) and positive ( Enterococcus faecium ) bacteria, representing frequent causes for MDR infections. Highly specific RNA capture probes for SNPs ( ampR D135G or ampR G154R ) or resistance genes ( vanA, vanB, and vanD ) allow to detect the binding of bacterial RNA within less than 5 min. Serial dilutions of bacterial RNA indicate an unprecedented sensitivity of 10 fg µL −1 total RNA corresponding to less than ten bacterial cells for SNPs and 1 fg µL −1 total RNA for vanD detection equivalent to single bacterial cell sensitivity. Abstract : A new nanosensor array method is presented to investigate antibiotic resistances in bacteria. Single nucleotide polymorphisms in ampicillin resistance markers from gram negative Pseudomonas aeruginosa and vancomycin resistance genes in gram positive Enterococcus faecium are studied. The method shows unprecedented sensitivity and specificity (1 bacterial cell) as well as drastically reduced times to obtain a diagnosis, compared to standard procedures.